2016
DOI: 10.4037/ajcc2016233
|View full text |Cite
|
Sign up to set email alerts
|

Cause of Death of Infants and Children in the Intensive Care Unit: Parents Recall vs Chart Review

Abstract: Background More than 55 000 children die annually in the United States, most in neonatal and pediatric intensive care units. Because of the stress and emotional turmoil of the deaths, the children’s parents have difficulty comprehending information. Objectives To compare parents’ reports and hospital chart data on cause of death and examine agreement on cause of death according to parents’ sex, race, participation in end-of-life decisions, and discussion with physicians; deceased child’s age; unit of care (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 25 publications
0
3
0
4
Order By: Relevance
“…1 CHD and chromosomal abnormalities account for approximately 20% of sudden deaths among neonates and infants (≤1 year old) and for nearly 5% among older children (1-18 years of age). 2 Epidemiologic studies have also indicated that cardiac arrest is associated with lower survival rates in neonates and infants than in children and adolescents, with rates of survival to hospital discharge less than 15% in several studies. [3][4][5][6] Cases of in-hospital arrest have a three-fold higher chance of survival than out-of-hospital cases (24 versus 8.4%).…”
mentioning
confidence: 99%
“…1 CHD and chromosomal abnormalities account for approximately 20% of sudden deaths among neonates and infants (≤1 year old) and for nearly 5% among older children (1-18 years of age). 2 Epidemiologic studies have also indicated that cardiac arrest is associated with lower survival rates in neonates and infants than in children and adolescents, with rates of survival to hospital discharge less than 15% in several studies. [3][4][5][6] Cases of in-hospital arrest have a three-fold higher chance of survival than out-of-hospital cases (24 versus 8.4%).…”
mentioning
confidence: 99%
“…Penelitian di Hospital Israelita Albert Einstein Brazil menunjukkan jumlah pasien yang masuk ruang PICU rata-rata 69,3% per tahun dan jumlah pasien terbanyak berada pada bulan April, Agustus, dan Oktober. Rata-rata lama tinggal di rumah sakit berkisar antara 9 sampai 19 hari (Brooten et al, 2016). Kelompok usia terbanyak yang masuk ruang PICU adalah usia 1 sampai 4 tahun (Brooten et al, 2016).…”
Section: Pendahuluanunclassified
“…Rata-rata lama tinggal di rumah sakit berkisar antara 9 sampai 19 hari (Brooten et al, 2016). Kelompok usia terbanyak yang masuk ruang PICU adalah usia 1 sampai 4 tahun (Brooten et al, 2016). Sekitar 55% dari semua anak yang meninggal di ruang PICU adalah laki-laki, usia ratarata adalah 2 tahun dan sepertiga berusia kurang dari satu tahun (Burns et al, 2014).…”
Section: Pendahuluanunclassified
See 2 more Smart Citations